2015
DOI: 10.1136/annrheumdis-2015-207526
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for treating rheumatoid arthritis to target: results of a systematic literature search update

Abstract: ObjectiveA systematic literature review (SLR; 2009–2014) to compare a target-oriented approach with routine management in the treatment of rheumatoid arthritis (RA) to allow an update of the treat-to-target recommendations.MethodsTwo SLRs focused on clinical trials employing a treatment approach targeting a specific clinical outcome were performed. In addition to testing clinical, functional and/or structural changes as endpoints, comorbidities, cardiovascular risk, work productivity and education as well as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
155
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(160 citation statements)
references
References 30 publications
1
155
0
4
Order By: Relevance
“…The Knevel et al 82 review also reported no particular benefit of TTT among patients with established RA, but an overall benefit of TTT among early RA patients. It is unclear whether or not the reviews by Schoels et al, 23 Stoffer et al 79 and Knevel et al 82 reported on all outcomes reported in all included studies; the current review provides an explicit and comprehensive overview of all measured outcomes. All five previous reviews examined data from RCTs and non-randomised studies together, whereas the current review focused on RCTs only, to reduce the possibility of selection bias.…”
Section: -78mentioning
confidence: 99%
See 1 more Smart Citation
“…The Knevel et al 82 review also reported no particular benefit of TTT among patients with established RA, but an overall benefit of TTT among early RA patients. It is unclear whether or not the reviews by Schoels et al, 23 Stoffer et al 79 and Knevel et al 82 reported on all outcomes reported in all included studies; the current review provides an explicit and comprehensive overview of all measured outcomes. All five previous reviews examined data from RCTs and non-randomised studies together, whereas the current review focused on RCTs only, to reduce the possibility of selection bias.…”
Section: -78mentioning
confidence: 99%
“…The systematic reviews by Schoels et al 23 (initial review) and Stoffer et al 79 (update of the Schoels et al review), designed to inform the international task force recommendations for treating to target, 17,18 both concluded that TTT was more effective than usual care. Similarly, Jurgens et al 21 examined the effectiveness of TTT on remission rates and found results in favour of TTT, Schipper et al 80 compared the effectiveness of TTT with usual care on mean change in DAS28 and found TTT to be more effective than usual care and Bakker et al 81 found evidence of the effectiveness of TTT in terms of remission, but did not synthesise the evidence (findings were reported individually by study).…”
Section: -78mentioning
confidence: 99%
“…Em vista disso, um dos principais objetivos da terapia atual é controlar rigorosamente o processo inflamatório, a fim de reduzir a atividade da doença e suas implicações [7,8].…”
Section: Introductionunclassified
“…Внедрение в клиническую практику новых эффектив-ных лекарственных средств, так называемых генно-инженерных биологических препара-тов (ГИБП), ингибиторов «сигнальных мо-лекул» и особенно совершенствование стра-тегии лечения РА с использованием стан-дартных базисных противовоспалительных препаратов (БПВП), в первую очередь мето-трексата (МТ), а также глюкокортикоидов (ГК), привело к кардинальному улучшению прогноза при этом заболевании [2,3]. В рам-ках стратегии «Лечение до достижения це-ли» (Treat To Target) задачей терапии РА яв-ляется не только симптоматическое улучше-ние состояния пациента, а достижение со-стояния клинической ремиссии [4,5], кото-рая обусловливает снижение риска потери трудоспособности, инвалидности и увеличе-ние продолжительности жизни пациентов до популяционного уровня [6]. Детальная характеристика и обоснование современных рекомендаций, касающихся лечения РА, представлены в предыдущих публикациях [2,3,7].…”
unclassified